Integrated Mechanisms of Polarity-Based Extracts of Cucumis melo L. Seed Kernels for Airway Smooth Muscle Relaxation via Key Signaling Pathways Based on WGCNA, In Vivo, and In Vitro Analyses - Muqeet Wahid; Fatima Saqib; Anam Ali; Abdulrahman Alshammari; Metab Alharbi; Abdur Rauf; Mohammad S. Mubarak (MDPI AG, 2022)
The present study aimed to determine the mechanisms responsible for calcium-mediated smooth muscle contractions in C. melo seeds. The phytochemicals of C. melo were identified and quantified with the aid of Liquid Chromatography Electrospray Ionization Tandem Mass Spectrometric (LC/ESI-MS/MS) and high-performance liquid chromatography (HPLC), and then tested in-vitro and in vivo to confirm involvement in smooth muscle relaxation. Allergic asthma gene datasets were acquired from the NCBI gene expression omnibus (GEO) and differentially expressed gene (DEG) analysis, weighted gene co-expression network analysis (WGCNA), and functional enrichment analysis were conducted. Additionally, molecular docking of key genes was carried out. Kaempferol, rutin, and quercetin are identified as phytochemical constituents of C. melo seeds. Results indicated that C. melo seeds exhibit a dose-dependent relaxant effect for potassium chloride (80 mM)- induced spastic contraction and calcium antagonistic response in calcium dose-response curves. The functional enrichment of WGCNA and DEG asthma-associated pathogenic genes showed cytokine-mediated pathways and inflammatory responses. Furthermore, CACNA1A, IL2RB, and NOS2 were identified as key genes with greater binding affinity with rutin, quercitrin, and kaempferol in molecular docking. These results show that the bronchodilator and antidiarrheal effects of C. melo were produced by altering the regulatory genes of calcium-mediated smooth muscle contraction.